New Directions in Corporate Governance Research - Hambrick, Donald C.; Werder, Axel v.; Zajac, Edward J. (Organization Science, 2008)
In this essay, we seek to identify the contributions that strategy and organizational researchers have made, and continue to make, in enhancing our understanding of a wide variety of important corporate governance questions. We begin by discussing how these research contributions stem from a willingness to draw from and contribute to different streams of intellectual thought, and we provide an orienting framework to situate this work.